(untitled) (Comprehensive Journal of Science, 2026)
In this study the and deformation parameters for the even-even 168-188W isotopes have been calculated by the electric transition probability and the intrinsic electric quadrupole moment respectively. our results have good agreement with the y-rast experimental results. This research showed that the maximum values of the deformation parameters of the under study isotopes were happened at and near the mid-shell(N=104).